2018
DOI: 10.21894/jopr.2018.0034
|View full text |Cite
|
Sign up to set email alerts
|

BIOCHEMICAL PROFILE OF BACTERISED CALLI AND EMBRYOGENIC CALLI OF OIL PALM (Elaeis guineensis Jacq.)

Abstract: Recent approaches have been made with regard to successful association of in vitro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Starch accumulation in embryogenic cells or in neighboring cells is related to the acquisition of embryogenic competence (Balzon et al, 2013;Silva et al, 2014;Lim et al, 2018). The starch produced in cells provides high levels of ATP, which is the energy source for cells and they are used in cell metabolism for intense cell division and subsequent development of embryos (Silva et al, 2014;Lim et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starch accumulation in embryogenic cells or in neighboring cells is related to the acquisition of embryogenic competence (Balzon et al, 2013;Silva et al, 2014;Lim et al, 2018). The starch produced in cells provides high levels of ATP, which is the energy source for cells and they are used in cell metabolism for intense cell division and subsequent development of embryos (Silva et al, 2014;Lim et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Starch accumulation in embryogenic cells or in neighboring cells is related to the acquisition of embryogenic competence (Balzon et al, 2013;Silva et al, 2014;Lim et al, 2018). The starch produced in cells provides high levels of ATP, which is the energy source for cells and they are used in cell metabolism for intense cell division and subsequent development of embryos (Silva et al, 2014;Lim et al, 2018). The presence and amount of starch can vary depending on the phase of embryo development because, during cell division and embryo development, this compound (starch) is consumed (Balzon et al, 2013).In embryogenic cells of Elaeisguineensis (Steinmacher et al, 2011;Pádua et al, 2013) storage of starch granules during embryogenesis is commonly observed.…”
Section: Discussionmentioning
confidence: 99%
“…Stress is one of the factors that promote embryogenic cell differentiation. Lim et al (2018a) reported that the detection of phenolic compounds in inoculated oil palm callus and embryogenic callus could be indicated as one of the stress factors for plant cells. The phenolic compounds benefit plant cells as modulators for IAA synthesis, where phenolic compounds inhibit the enzymatic oxidation of IAA and results in plant cell division and differentiation (Loṕez Arnaldos et al, 2001).…”
Section: Pgpr Promotes Somatic Embryogenesismentioning
confidence: 99%
“…To promote plant growth, one of the important compounds is amino acid, which is essential in protein synthesis (Vidal and Gutierrez, 2008). Lim et al (2018a) showed an increase in total amino acid content and biomass at day 30 after treatment of callus with H. seropedicae Z78 pellet cells, suggesting an accelerated rate of formation of friable embryogenic callus. The increase in total free amino acids in tissue may be due to increased metabolic activities in plant cultures, leading to cell division and increased cellular biomass in somatic embryogenesis (Feher et al, 2003).…”
Section: Biochemical Activities Of Inoculated In Vitro Oil Palmmentioning
confidence: 99%
See 1 more Smart Citation